Analysis of the Effectiveness and Contribution of Customs Tax Land Rights Building and Land Tax Building Maintenance and Improvement of the Indigenous People of South Aceh - Lingga, Fitria Ratna; Nurwani, Nurwani; Syarvina, Wahyu (Dinasti Publisher, 2024)
This study aims to determine the effectiveness and contribution of Tax Customs acquisition of land and building rights (BPHTB) and Urban and rural land and Building Tax (PBB-P2) to the receipt of local revenue (PAD) from 2018-2022. This research method uses a qualitative method that uses a descriptive approach. The object of this study is the Office of the Financial Management Agency of South Aceh region, the source of data used is secondary and primary data, secondary data obtained from the realization of the effectiveness and contribution of tax revenues acquisition of land and building duty (BPHTB) and land tax and Urban and rural building (PBB-P2),and primary data obtained from interviews. Based on the results of the discussion, the level of effectiveness of BPHTB from 2018-2022 is very effective with a percentage level of 167.45%, while the level of contribution is in the good category with a percentage of 45%. For the level of effectiveness of PBB-P2 from 2018-2022, it is quite effective with a value of 80.36%. While the level of contribution is in the medium category with a percentage value of 23%.